2022
DOI: 10.1111/rda.14283
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasonography, progesterone assay, ballottement, and non‐return‐to‐heat with digital rectal palpation technique for early pregnancy diagnosis in Red Sokoto goat

Abstract: Early pregnancy diagnosis is of considerable economic value in the livestock industry. In recent years, there has been increasing awareness of the need for early detection of pregnancy in goats. Pregnancy examination in goats may be requested by the owner, who would like to know the pregnancy status of the doe. Perhaps, the most important reason for pregnancy diagnosis is the detection of non-pregnancy, pseudo-pregnancy, or hydrometra, which may occur in pet and commercial goats, especially in dairy herds wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…It requires common and simple materials for the procedure, adoptable and safe, and holds a great prospect and potentials for the goat industry. Pregnancy rates obtained in this study were high and acceptable, comparable, agree and confirms the reports of Kutty (1999), Abou-El-Roos and Shawki ( 2003), Bello et al (2012), Bello (2019) and Bello et al, (2022a), where similar values on days 21 to 30 postservice were reported. Besides, the results indicated uterine distension was palpated and identified earlier on days 14 and 21 after mating than the 28 to 30 days reported (Abou-El-Roos and Shawki, 2003;Bello, 2019; The good response rate generally, but notably for the natural service group C was challenging for the two bucks initially designated to minimize influence of buck on fertility, and breeding intended to be spread over seven days.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It requires common and simple materials for the procedure, adoptable and safe, and holds a great prospect and potentials for the goat industry. Pregnancy rates obtained in this study were high and acceptable, comparable, agree and confirms the reports of Kutty (1999), Abou-El-Roos and Shawki ( 2003), Bello et al (2012), Bello (2019) and Bello et al, (2022a), where similar values on days 21 to 30 postservice were reported. Besides, the results indicated uterine distension was palpated and identified earlier on days 14 and 21 after mating than the 28 to 30 days reported (Abou-El-Roos and Shawki, 2003;Bello, 2019; The good response rate generally, but notably for the natural service group C was challenging for the two bucks initially designated to minimize influence of buck on fertility, and breeding intended to be spread over seven days.…”
Section: Discussionsupporting
confidence: 92%
“…Pregnancy rate for DRP increased significantly from day 14 to day 126 across groups with highest rates on day 28; suggesting early pregnancy diagnosis in Red Sokoto goat does, day 28 may be the standard. However, Bello et al (2022a;2012) reported similar findings on day 21 for the breed, which agrees with report of Abou-El-Roos and Shawki ( 2003) in ewes on day 30. The low rate on day 14 in group A was attributed to inexperience and lack of skills, palpation usually starts from group A to C. The mistakes and learning took place in group A, when procedure was being carried out in groups B and C, some level of skill perfection was achieved.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations